Advanced Additive Manufacturing 2022
DOI: 10.5772/intechopen.101859
|View full text |Cite
|
Sign up to set email alerts
|

Nanometric 3D Printing of Functional Materials by Atomic Layer Deposition

Abstract: Atomic layer deposition (ALD) is a chemical vapour deposition (CVD) method that allows the layer-by-layer growth of functional materials by exposing a surface to different precursors in an alternative fashion. Thus, thanks to gas-solid reactions that are substrate-limited and self-terminating, precise control over thickness below the nanometer level can be achieved. While ALD was originally developed to deposit uniform coatings over large areas and on high-aspect-ratio features, in recent years the possibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…These coatings are often deposited by spin-coating or by vacuum-based techniques such as atomic layer deposition (ALD) or sputtering and very often exhibit scalability issues for AgNW-based TEs. ALD is a thin film deposition technique allowing for the preparation of conformal and high quality films at the nanoscale and on complex substrates. Atmospheric pressure spatial ALD (AP-SALD) is a recently developed alternative to ALD that allows deposition rates up to 2 orders of magnitude faster than conventional ALD, under atmospheric conditions, and lower temperatures. ,, To improve the stability of AgNW networks, nanocomposites with several types of oxides deposited by AP-SALD have already been studied in our previous works. Among the studied oxides there are ZnO, , bilayers of zinc oxide/alumina (ZnO/Al 2 O 3 ), and aluminum-doped zinc oxide (AZO) .…”
Section: Introductionmentioning
confidence: 99%
“…These coatings are often deposited by spin-coating or by vacuum-based techniques such as atomic layer deposition (ALD) or sputtering and very often exhibit scalability issues for AgNW-based TEs. ALD is a thin film deposition technique allowing for the preparation of conformal and high quality films at the nanoscale and on complex substrates. Atmospheric pressure spatial ALD (AP-SALD) is a recently developed alternative to ALD that allows deposition rates up to 2 orders of magnitude faster than conventional ALD, under atmospheric conditions, and lower temperatures. ,, To improve the stability of AgNW networks, nanocomposites with several types of oxides deposited by AP-SALD have already been studied in our previous works. Among the studied oxides there are ZnO, , bilayers of zinc oxide/alumina (ZnO/Al 2 O 3 ), and aluminum-doped zinc oxide (AZO) .…”
Section: Introductionmentioning
confidence: 99%
“…This SALD approach is particularly versatile since it can be easily tuned by simply modifying the manifold injector. For instance, we have shown that 3D printing can be used to customize close-proximity SALD manifolds in different materials, opening up a large span of possibilities. , …”
Section: Introductionmentioning
confidence: 99%